การประเมินการจัดการเรียนการสอนออนไลน์ในรายวิชาเลือกภาษาอังกฤษของ มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตสุราษฎร์ธานี: An Evaluation of the Online Elective English Courses of Prince of Songkla University, Surat Thani Campus - Asama Tasanameelarp อัสมา ทรรศนะมีลาภ; Tuna Girgin ทูน่า เกอร์กิ้น; Thachapan Kesornsit ธัชพรรณ เกษรสิทธิ์ (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2022)
The purposes of this study were to investigate students’ satisfaction and online learning problems in English elective courses at Prince of Songkla University, Surat Thani campus. A mixed-methods approach was used to collect data. The questionnaire with a five-Likert scale was administered to 130 students who had enrolled in English elective courses. Of these, 20 students volunteered to be interviewed to obtain further information. Numerical data showed that the three categories with which participants were most satisfied were as follows: (1) Course Objectives ( =3.70), (2) Assessment and Evaluation ( =3.60), and (3) Teachers and Teaching Methods ( =3.60). The interview results provided further useful information about the participants’ satisfaction with the English elective courses with should be taken into consideration to improve the English elective courses. This course evaluation research provides teachers with practical recommendations on enhancing their classes’ teaching/learning circumstances, directly affecting students. The evaluation results assist the teachers in improving their teaching and aligning their courses and tests.